Reliability and validity of a dual-probe personal computer-based muscle viewer for measuring the pennation angle of the medial gastrocnemius muscle in patients who have had a stroke. Issue 1 (2nd January 2018) - Cho, Ji-Eun; Cho, Ki Hun; Yoo, Jun sang; Lee, Su Jin; Lee, Wan-Hee
Abstract: Background: A dual-probe personal computer-based muscle viewer (DPC-BMW) is advantageous in that it is relatively lightweight and easy to apply. Objective: To investigate the reliability and validity of the DPC-BMW in comparison with those of a portable ultrasonography (P-US) device for measuring the pennation angle of the medial gastrocnemius (MG) muscle at rest and during contraction. Methods: Twenty-four patients who had a stroke (18 men and 6 women) participated in this study. Using the DPC-BMW and P-US device, the pennation angle of the MG muscle on the affected side was randomly measured. Two examiners randomly obtained the images of all the participants in two separate test sessions, 7 days apart. Intraclass correlation coefficient (ICC), confidence interval, standard error of measurement, Bland-Altman plot, and Pearson correlation coefficient were used to estimate their reliability and validity. Results: The ICC for the intrarater reliability of the MG muscle pennation angle measured using the DPC-BMW was > 0.916, indicating excellent reliability, and that for the interrater reliability ranged from 0.964 to 0.994. The P-US device also exhibited good reliability. A high correlation was found between the measurements of MG muscle pennation angle obtained using the DPC-BMW and that obtained using the P-US device ( p  < 0.01). Conclusion: The DPC-BMW can provide clear images for accurate measurements, including measurements using dual probes. It has the advantage of rehabilitative US imaging for individuals who have had a stroke. More research studies are needed to evaluate the usefulness of the DPC-BMW in rehabilitation.